Public Service Satisfaction Analysis in Village and District: A Comprehensive Examination - Pratama, Ivano Aditya; Sukmana, Hendra (Indonesian Journal of Public Policy Review, 2023)
This study investigates community satisfaction with public services in Banjarasri Village, Tanggulangin District, Sidoarjo Regency, employing a qualitative descriptive design with a mix of qualitative and quantitative methods. Using a sample of 334 randomly selected respondents, the research assesses satisfaction across nine indicators outlined in the Decree of the Minister for Administrative Reform and Bureaucratic Reform. While overall satisfaction is observed, the study reveals a neutral sentiment towards service time, indicating a need for improvement in this specific aspect. The average value of 3.17 suggests a positive community response. The implications of these findings underscore the importance of enhancing service time to further elevate public satisfaction with local services, contributing to the broader discourse on effective public administration.Highlight : Comprehensive Assessment: This study conducts a thorough evaluation of community satisfaction with public services in Banjarasri Village, encompassing various dimensions outlined in the Ministerial Decree. Service Time Neutral Outlook: The research identifies a neutral sentiment towards service time, emphasizing the critical need for targeted improvements in this specific aspect of public service delivery. Mixed Methods Approach: Employing a qualitative descriptive design with a mix of qualitative and quantitative methods, the study provides a nuanced understanding of community perceptions, offering valuable insights for local governance and public administration Keywords: Community Satisfaction, Public Services, Qualitative Research, Service Time, Local Governance